2016
DOI: 10.1161/circulationaha.115.018544
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and the Efficacy and Safety of Rivaroxaban Versus Warfarin in the Prevention of Stroke in Patients With Nonvalvular Atrial Fibrillation

Abstract: M ultiple medications are common in the treatment of adult patients. This is particularly true in elderly patients with chronic medical conditions such as atrial fibrillation (AF). The use of multiple medications in a single patient, called polypharmacy, is becoming more prevalent in contemporary, guidelinedriven practice. Continuing medical education (CME) credit is available for this article. Go to http://cme.ahajournals.org to take the quiz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
225
1
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(263 citation statements)
references
References 17 publications
22
225
1
15
Order By: Relevance
“…There is some evidence that polytherapy may be associated with a reduced clinical benefit of AP and with increased bleeding risk in patients receiving RI [90,91].…”
Section: Conditions Associated With High Risk Of Bleedingmentioning
confidence: 99%
“…There is some evidence that polytherapy may be associated with a reduced clinical benefit of AP and with increased bleeding risk in patients receiving RI [90,91].…”
Section: Conditions Associated With High Risk Of Bleedingmentioning
confidence: 99%
“…54 Similarly, in the re-analysis of the ROCK-ET-AF trial, patients taking more than 10 drugs showed a non-significant trend of increased risk of major and minor bleeding, in the absence of stroke/SE modifications, compared to patients taking up to 4 drugs. 55 Moreover, patients on multidrug therapy have been shown to adhere less to therapy regimen than patients on little drug therapy. Contrary to Warfarin, for which about 36% of the patients have been shown not taking more than 20% of the planned doses, 56 all NOACs have demonstrated a good therapeutic adherence in over 85% of patients in real world clinical practice.…”
Section: Knowledge Gaps and Discussionmentioning
confidence: 99%
“…В исследо-вании ROCKET AF 0-4 исходно, помимо антикоагулянтов, до 4 лекарственных средств получали 36% больных, от 5 до 9 -51%, 10 и более -15% [23]. В целом увеличение числа принимаемых препаратов, особенно до 10 и более, было сопряжено с более высоким риском кровотечений и смерти, однако результаты сравнения ривароксабана и варфарина по первичным конечным точкам, характери-зующим эффективность и безопасность, не зависели от числа лекарственных средств, применявшихся в начале лечения.…”
Section: результаты анализа подгрупп в исследовании Rocket Afunclassified